I Can haz Stail: a Language Style of LOLcat Meme in icanhas.cheezburger.com - Daniel P. Laksono; Adventina Putranti (Journal of Language and Literature, 2016)
The viral phenomenon of LOLcat meme makes many researchers study this internet meme. Although its words and sentences are unconventional, people can apply this unconventional English so that the meme became viral. It is even used in other forms of meme such as Bible, books, and a musical theater. The fact that the English is unconventional but makes the meme viral is what inspires this study. Henceforth, this study aims to find reasons how such unconventional English syntax strengthen the virality of LOLcat meme.